A Qualitative Needs Analysis of English for Biology Students in Academic and Research Contexts - Akhrif Yahsya (Educazione: Journal of Education and Learning, 2024)
English plays an increasingly important role in biology education as students are required to access international scientific literature, conduct research, and communicate scientific findings. However, English courses offered in many Biology Education programs continue to emphasize General English, which may not adequately address students' academic and disciplinary needs. This study aimed to explore the English language needs of Biology Education students within academic and research contexts through the lens of English for Specific Purposes (ESP). A qualitative descriptive design was employed, involving semi-structured interviews with six undergraduate Biology Education students and one Biology lecturer at State Islamic College of Mandailing Natal (STAIN Mandailing Natal), who were selected using purposive sampling based on their direct involvement in biology teaching, learning, and academic research. The collected data were analyzed using Braun and Clarke's thematic analysis. Four major themes emerged from the analysis: (1) English as an essential tool for accessing scientific literature and laboratory resources, (2) challenges in understanding scientific terminology and producing academic English, (3) the mismatch between General English instruction and Biology students' disciplinary needs, and (4) expectations for an English for Biology curriculum emphasizing academic reading, scientific writing, oral presentation, and research communication. The findings demonstrate that Biology Education students require English not merely for everyday communication but primarily for developing academic literacy and research competence. The study suggests that English courses in Biology Education should be redesigned based on systematic needs analysis and aligned with authentic disciplinary communication. Such curriculum development is expected to better prepare students for undergraduate research, scientific publication, and participation in international academic communities.